THE Magical Realism in Garcia’s "One Hundred Years of Solitude " as a Reflection of the Political Climate - Jaafar, Jihad (International Journal of Language and Literary Studies, 2023)
This research explores the use of magical realism in this novel as a reflection of the political climate. The aims of the study are to analyze how magical realism functions as a narrative technique, to examine its role in depicting the political landscape, and to understand the implications of this literary style on the reader’s perception of reality. The methodology employed is primarily qualitative. The novel is analyzed through a literary lens, focusing on the narrative techniques and the elements of magical realism. The discussion section delves into the ways in which magical realism serves as a reflection of the political climate. The analysis reveals that the author utilizes magical elements to metaphorically represent the complex and turbulent political events occurring in Latin America during the time period. The results of the research highlight the profound impact of magical realism in conveying political themes and creating a unique narrative experience. The study demonstrates how magical realism offers a lens through which readers can critically engage with the political climate of the era. In conclusion the author crafts a narrative that not only captures the historical context but also explores the human experience within a tumultuous political landscape.